A study of defect pattern analysis in school building / Norliana Ahmad Zaidi - Ahmad Zaidi, Norliana (Faculty of Architecture, Planning and Surveying, 2013)
A defect may be considered as shortcoming or failing towards function, performance, statutory or user requirements of a building. It might manifests itself within the structure, fabrics, services or other facilities of the affected building. The objectives and goals that to be achieved from this study to identify and analyze types of defect in school building, to make comparison of defect pattern between building age more than 25 years and less than 25years and to study the causes of the structure defects and analyze the defect pattern. The principle of diagnosis before analyzing the result should takes a few steps where the first step need to be take into account is the information that need to be obtain are about the site, geology, drainage, and former uses. Then, inspecting the defect and take measurement while carry out in-situ testing .Finally, carry out labotary test and employ clear analytical methods. The information of data collection is gathered from condition survey works on six respective schools and the result obtain will be interpreted in graphical method a a comparison between six schools. As an overall conclusion, it can be conclude that in comparing between schools buildings aged less than 10 years with school building more than 25 years, the defect pattern shows that most of the major-base defect occurred in school building aged more than 25 years